2003
DOI: 10.1063/1.1566089
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical leakage currents as a possible origin of the polarization offsets observed in compositionally graded ferroelectric films

Abstract: Multiferroic response of nanocrystalline lithium niobate J. Appl. Phys. 111, 07D907 (2012) Non-radiative complete surface acoustic wave bandgap for finite-depth holey phononic crystal in lithium niobate Offsets of hysteresis loops along the polarization axis have been observed on a step graded Pb͑Zr,Ti͒O 3 ͑PZT͒ thin film using a Sawyer-Tower ͑ST͒ circuit. However, the same effect may be artificially reproduced by adding adequate resistors and diodes in parallel with a nongraded PZT thin film. The hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 31 publications
4
43
2
Order By: Relevance
“…The superscript ''Ϯ'' denotes f may take different values for E f Ͼ0 ͑represented by ''ϩ''͒ and E f Ͻ0 ͑represented by ''Ϫ''͒. This usage is consistent with the notation adopted by Zheng et al 15 and Bouregba et al 30 Using Eqs. ͑1͒-͑3͒, we obtain, after some manipulation,…”
Section: Ferroelectric-dielectric Layered Modelsupporting
confidence: 62%
See 3 more Smart Citations
“…The superscript ''Ϯ'' denotes f may take different values for E f Ͼ0 ͑represented by ''ϩ''͒ and E f Ͻ0 ͑represented by ''Ϫ''͒. This usage is consistent with the notation adopted by Zheng et al 15 and Bouregba et al 30 Using Eqs. ͑1͒-͑3͒, we obtain, after some manipulation,…”
Section: Ferroelectric-dielectric Layered Modelsupporting
confidence: 62%
“…A composite possesses effective dielectric and ferroelectric properties, and we imagine this ''effective'' sample is placed in the Sawyer-Tower circuit. Figure 5 ϩ (sat) generally obeys a power law, 30,34,35 i.e., D o f f (sat)ϰE A ϩ (sat) n , 2ՇnՇ5, which differ from the present results. The possible reason is that, in our calculation, f ϩ and f Ϫ are assumed to be constants independent of E A ϩ (sat).…”
Section: B Polarization Offsets In Ferroelectrics With Asymmetric Cocontrasting
confidence: 57%
See 2 more Smart Citations
“…This is also the range of experimental measurements where notable vertical shifts of the hysteresis loop are reported in the literature. [12][13][14][15] In our previous study of compositionally graded ferroelectric films, we have already demonstrated that the polarization gradient across a ferroelectric film can lead to asymmetric conduction, which we believe provides a mechanism for the polarization offset phenomenon. Now it is worth further examining the asymmetric conduction current.…”
Section: B Effect Of Charge-carrier Mobilities and Film Thicknessmentioning
confidence: 99%